Avaliação da atividade larvicida e de oviposição do óleo essencial de Eryngium foetidum L. combinado com fibroína de seda frente às larvas de Aedes aegypti - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2025)
The Aedes aegypti mosquito is a vector for significant arboviruses, including dengue, chikungunya, Zika, and yellow fever, posing a major public health challenge. The indiscriminate use of synthetic insecticides has led to mosquito resistance, along with environmental harm and adverse effects on non-target organisms. In this context, this study aimed to evaluate the larvicidal activity and oviposition behavior of a nanoformulation containing Eryngium foetidum essential oil and silk fibroin against third-instar Ae. Aegypti larvae. The nanoformulation exhibited a mean particle size of 314.4 ± 70.47 nm, a polydispersity index of 0.521 ± 0.24, and a zeta potential of -37.8 ± 2.42 mV, indicating suitable stability. Results demonstrated promising larvicidal activity, with an LC50 of 55.73 μg·mL⁻¹ after 24 hours of exposure, as well as significant inhibition of female oviposition. These findings suggest that the developed nanoformulation could serve as a sustainable and effective alternative for vector control, emerging as a highly promising biomaterial for public health applications.
Keywords: Chicória; Compostos bioativos; Bioinseticida; Controle larvicida; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA; ODS 3 – Saúde e bem-estar; ODS 12 – Consumo e produção responsáveis